2014
DOI: 10.1002/adsc.201400609
|View full text |Cite
|
Sign up to set email alerts
|

Carbocations as Lewis Acid Catalysts: Reactivity and Scope

Abstract: One class of potential Lewis acids that has received negligible attention as a catalyst is the carbocation. Here we show the potential of triarylmethylium ions as highly powerful Lewis acid catalysts for organic reactions. The Lewis acidity of the triarylmethylium ion can be easily tuned by variation of the electronic properties of the aromatic rings and the catalytic activity of the carbocation is shown to correlate directly to the level of stabilization of the empty p C -orbital at the cationic carbon. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 44 publications
0
31
0
3
Order By: Relevance
“…[12,19] As expected, the oxo-metathesis became slower as the electron density of one of the aromatic rings increased (i.e., decreasing the Lewis acidity of the carbocation) on going from trityl to a mono-methyl-(4) to mono-methoxy-substituted (5) trityl cation ( Table 2, entries 9-12). Unfortunately, decreasing the Lewis acidity of the trityl ion did not prevent any side-reactions and had a negative effect on the yield.…”
Section: Optimization Of the Reaction Conditionsmentioning
confidence: 70%
See 1 more Smart Citation
“…[12,19] As expected, the oxo-metathesis became slower as the electron density of one of the aromatic rings increased (i.e., decreasing the Lewis acidity of the carbocation) on going from trityl to a mono-methyl-(4) to mono-methoxy-substituted (5) trityl cation ( Table 2, entries 9-12). Unfortunately, decreasing the Lewis acidity of the trityl ion did not prevent any side-reactions and had a negative effect on the yield.…”
Section: Optimization Of the Reaction Conditionsmentioning
confidence: 70%
“…[11][12][13][14][15][16] In fact, the application of carbocations as Lewis acid catalysts is poorly studied and we reasoned that the carbocation might have properties different to those of metal-or metalloid-based Lewis acid catalysts. With this in mind we set out to evaluate the trityl cation in the reaction reported by Bickelhaupt and co-workers.…”
Section: Optimization Of the Reaction Conditionsmentioning
confidence: 99%
“…The trityl ion constitutes a rather unique center of Lewis acidity that can be easily tuned by alteration of the electronic properties of the pendant aromatic rings 14a,14b. As expected, the rate of reaction decreased as electron density of the aromatic ring increased (e.g., decreasing Lewis acidity of the carbocation), going from hydrogen to methoxy (Table 1, entry 4).…”
Section: Resultsmentioning
confidence: 61%
“…In the course of our work we found that the trityl ion [e.g. triphenylcarbenium tetrafluoroborate (TrBF 4 )] is highly efficient for the activation of α,β‐aldehydes and tosyl imines in the Diels–Alder reaction14a,14b and the aza‐Diels–Alder reaction,14b respectively (Scheme , a and b).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the enormous electrophilicity of these Lewis acids could be incompatible with the relatively electron‐rich naphthyl groups in [ 4 ] – . We therefore also considered testing the corresponding trityl salt [Ph 3 C] + · [ 4 ] – as catalyst in asymmetric Diels–Alder reactions . Franzén and coworkers had recently shown that trityl cations promote challenging Diels–Alder reactions of cyclohexa‐1,3‐diene,[17a], [17b] and the same group accomplished a related enantioselective Diels–Alder reaction of 2,3‐dimethylbuta‐1,3‐diene, directed by a chiral counteranion.…”
Section: Introductionmentioning
confidence: 99%